(3GdEjVGM aj GdJaSjQs - (3ESeGYjd Hf eMeO Hf GdaVd Hf Ydj GdbQTj CHh GdbGSe GdWdjMj GdJejej, bhGe GdSfI,J (B535 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYGde dYhGbH GdCehQ GdeWdY Ydi eG ai GdUOhQ hbO cfJ LeYJ cJGHkG ai GdJaSjQ s
(3BNQgG (B:s
(3bGd SYjO Hf LQjQ QMeg Gddg Ci dGjQGA hbGd GdMSf QMeg Gddg jTQc ai GdYed hGdfGS (B( (3ef JaSjQ ShQI GdfGS BNQ GdbQBf (B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B323 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B293s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(4011) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs